Factors Predicting Oncological Outcomes of Radical Nephroureterectomy for Upper Tract Urothelial Carcinoma in Taiwan - Chen, I-Hsuan Alan; Chang, Chao-Hsiang; Huang, Chi-Ping; Wu, Wen-Jeng; Li, Ching-Chia; Chen, Chung-Hsin; Huang, Chao-Yuan; Lo, Chi-Wen; Yu, Chih-Chin; Tsai, Chung-You; Wu, Wei-Che; Tseng, Jen-Shu; et al. (Frontiers in Oncology, 2022)
Background: Taiwan is one of the endemic regions where upper tract urothelial carcinoma (UTUC) accounts for approximately a third of all urothelial tumors. Owing to its high prevalence, extensive experience has been accumulated in minimally invasive radical nephroureterectomy (RNU). Although a variety of predictive factors have been explored in numerous studies, most of them were on a single-center or limited institutional basis and data from a domestic cohort are lacking. Objective: To identify significant predicting factors of oncological outcomes, including overall survival (OS), cancer-specific survival (CSS), disease-free survival (DFS) and intravesical recurrence-free survival (IVRFS), following RNU for UTUC in Taiwan. Methods: A multicenter registry database, Taiwan UTUC Collaboration Group, was utilized to analyze oncological outcomes of 3333 patients undergoing RNU from 1988 to 2021 among various hospitals in Taiwan. Clinicopathological parameters were recorded according to the principles established by consensus meetings. The Kaplan-Meier estimator was utilized to estimate the survival rates and the curves were compared using the stratified log-rank test. Univariate and multivariate analyses were performed with the Cox proportional hazard model to explore potential predicting factors. Results: With a median follow-up of 41.8 months in 1808 patients with complete information, the 5-year IVRFS, DFS, CSS and OS probabilities were 66%, 72%, 81% and 70%. 482 patients experienced intravesical recurrence, 307 died of UTUC and 583 died of any cause. Gender predominance was female (57%). 1531 patients (84.7%) had high-grade tumors; preoperative hydronephrosis presented in 1094 patients (60.5%). Synchronous bladder UC was identified in 292 patients (16.2%). Minimally invasive procedures accounted for 78.8% of all surgeries, including 768 hand-assisted laparoscopic (42.5%), and 494 laparoscopic (27.3%) approaches. Synchronous bladder UC was the dominant adverse predicting factor for all survival outcomes. Other independent predicting factors for OS, CSS and DFS included age ≧70, presence of preoperative hydronephrosis, positive surgical margin, LVI, pathological T and N staging, and laparoscopic RNU. Conclusion: Synchronous UC of the urinary bladder is an independent adverse prognostic factor for survival in UTUC. The presence of preoperative hydronephrosis was also corroborated as a disadvantageous prognostic factor. Our multivariate analysis suggested that laparoscopic RNU might provide better oncological control.